2017
DOI: 10.1093/brain/awx148
|View full text |Cite
|
Sign up to set email alerts
|

Slow wave sleep disruption increases cerebrospinal fluid amyloid-β levels

Abstract: See Mander et al. (doi:10.1093/awx174) for a scientific commentary on this article.Sleep deprivation increases amyloid-β, suggesting that chronically disrupted sleep may promote amyloid plaques and other downstream Alzheimer's disease pathologies including tauopathy or inflammation. To date, studies have not examined which aspect of sleep modulates amyloid-β or other Alzheimer's disease biomarkers. Seventeen healthy adults (age 35-65 years) without sleep disorders underwent 5-14 days of actigraphy, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
338
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 474 publications
(348 citation statements)
references
References 34 publications
8
338
0
2
Order By: Relevance
“…1 Sleep restriction accelerates and sleep enhancement decelerates beta-amyloid plaque formation in an Alzheimer disease mouse model. 3 SWS could counteract accumulation of beta-amyloid, and potentially alpha-synuclein, through glymphatic clearance 4 or reduced production. 3 SWS could counteract accumulation of beta-amyloid, and potentially alpha-synuclein, through glymphatic clearance 4 or reduced production.…”
mentioning
confidence: 99%
“…1 Sleep restriction accelerates and sleep enhancement decelerates beta-amyloid plaque formation in an Alzheimer disease mouse model. 3 SWS could counteract accumulation of beta-amyloid, and potentially alpha-synuclein, through glymphatic clearance 4 or reduced production. 3 SWS could counteract accumulation of beta-amyloid, and potentially alpha-synuclein, through glymphatic clearance 4 or reduced production.…”
mentioning
confidence: 99%
“…8 Individuals (n = 4) with abnormally low Aβ42 levels (<608 pg/ml) indicating amyloid plaques were excluded from analyses of Aβ40 or Aβ42. 6,8 Statistical Analysis (Table 1). 6,8 Statistical Analysis (Table 1).…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…We previously showed that OSA may impair Aβ clearance and affect the relationship between slow wave activity (SWA) and Aβ. 4,5 Preliminary studies suggest slow wave activity (SWA) may modulate soluble Aβ; selective SWA deprivation increases Aβ, 6 whereas partial sleep deprivation with preserved SWA does not affect Aβ. OSA treatment increased SWA, and SWA was significantly correlated with lower Aβ after treatment.…”
mentioning
confidence: 99%
“…Sleep deprivation for one night [41] or interruption of non-REM sleep [42] in healthy subjects has been shown to increase levels of Aβ 1–42 and Aβ 1–40 in cerebrospinal fluid (CSF). In mice, sleep deprivation caused increases in Aβ peptides in brain interstitial fluid [43], and a direct relationship was established between Aβ and wakefulness.…”
Section: Sleep Disturbances In Admentioning
confidence: 99%